Targeting Glutathione and Cystathionine β-Synthase in Ovarian Cancer Treatment by Selenium-Chrysin Polyurea Dendrimer Nanoformulation - Santos, Inês (2019)
The research was funded by iNOVA4Health UID/Multi/04462, a program financially supported by Fundação para a Ciência e Tecnologia/Ministério da Educação e Ciência (FCT-MCTES), through national funds, and co-funded by FEDER under the PT2020 Partnership Agreement. We also acknowledge funding from FCT-MCTES through project DREAM PTDC/MEC-ONC/29327/2017.